Investigating metacognitive reading strategy awareness of Saudi tertiary students : comparisons of gender, reading ability and year level - Khreisat, Mohammad Nayef (Penerbit Universiti Kebangsaan Malaysia, 2022)
Students entering higher education are required to have higher order reading skills in order to succeed at the tertiary level. Comprehending complex texts requires them to possess certain strategies to compensate for any pitfalls of not grasping unfamiliar words or semantic structures especially in first-time read texts. The study, therefore, investigated the metacognitive reading strategy awareness of EFL Saudi students at the tertiary level in Saudi Arabia and its relationship with other variables such as year level and gender. A total of 355 students completed the Metacognitive Awareness of Reading Strategies Inventory (MARSI-R) (Mokhtari et al., 2018). The data analysis delineated metacognitive awareness of EFL Saudi students of reading strategies and variations in awareness and use between different levels and genders. The most and least frequently used strategies among the students and correlation between different strategies and year and ability perception levels were also analysed. The findings indicated that the participants in this study had a medium level of awareness in all metacognitive reading strategies. The analysis also showed that the most frequently used strategy amongst Saudi students was problem-solving strategies (PSS) followed by support reading strategies (SRS) and the least frequently used strategy was global reading strategies (GRS). Awareness among students according to their perceived levels varied but only result of poor readers was statistically lower compared to other levels. Gender differences were all statistically insignificant across all subscales of reading strategies. The study concludes with a number of suggested pedagogical implications and future research recommendations.